2023
DOI: 10.1021/acs.langmuir.3c00507
|View full text |Cite
|
Sign up to set email alerts
|

α-Amino Acids as Reducing and Capping Agents in Gold Nanoparticles Synthesis Using the Turkevich Method

Aleksandra M. Figat,
Bartosz Bartosewicz,
Malwina Liszewska
et al.

Abstract: Amino acid-capped gold nanoparticles (AuNPs) are a promising tool for various applications, including therapeutics and diagnostics. Most often, amino acids are used to cap AuNPs synthesized with other reducing agents. However, only a few studies have been dedicated to using α-amino acids as reducing and capping agents in AuNPs synthesis. Hence, there are still several gaps in understanding their role in reducing gold salts. Here, we used 20 proteinogenic α-amino acids and one non-proteinogenic α-amino acid in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…It has been reported that certain amino acids are selectively adsorbed on the crystal faces of AuNPs. This might also affect the growth and connection of AuNPs on a substrate. , These factors account for the differences in the amino acids that are appropriate for the growth of AuNPs on a substrate and for the synthesis of AuNPs in bulk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that certain amino acids are selectively adsorbed on the crystal faces of AuNPs. This might also affect the growth and connection of AuNPs on a substrate. , These factors account for the differences in the amino acids that are appropriate for the growth of AuNPs on a substrate and for the synthesis of AuNPs in bulk.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, the reducing agents suitable for the growth of AuNPs immobilized on the substrate differed from those used for synthesizing large AuNPs in bulk, as reported in previous studies. Figat et al reported the synthesis of AuNPs using all the α-amino acids except for Pro, Cys, Gln, and Arg . They found that when used as both reducing and stabilizing agents, Thr, Gly, Leu, and Ala produced larger AuNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free À COOH and À NH 2 functional groups are known to participate in the reduction process. [22] TEM image after the growth reaction with peptide suggests a slight variation in the MGS (Figure 7B). The disk floret part in presence of peptide is comparable with the TEM obtained from Met mediated growth.…”
Section: Extension Of Growth Reaction Strategy To Met Rich Peptides F...mentioning
confidence: 99%
“…Among all nanomaterials, the gold nanoparticles (AuNPs) are proven to be safest and less toxic which make them superior for biomedical applications such as targeted drug delivery, diagnostics, plasmonic biosensing, tissue engineering and cancer therapy. [1][2][3][4][5][6] The unique size dependent optical properties of AuNP are well exploited in surface enhanced Raman scattering (SERS) which is strong tool to enhance the Raman signal of molecule adsorbed on a nanosurface. [7][8][9] The SERS enhancement mechanism originates both from electromagnetic effect and chemical charge transfer between adsorbing molecule and metal surface.…”
Section: Introductionmentioning
confidence: 99%